Preparation and physical-chemical and sensorial analyzes of red jambo jam in syrup (REMUNOM, 2024)
The red jambo (Syzygium malaccense) is an exotic fruit and ornamental tree that is widely cultivated inthe North and Northeast regions of Brazil. Its fruit, the jambo, is very rich in various nutrients, but there isa short period for consumption after harvesting. This work aimed to prepare a sweet red jambo in syrup asa way of extending the time available for consumption of the fruit, and to sensorially analyze the productproduced. The results show that the sweet produced has high acceptance, which is indistinct between menand women.